Early breastfeeding initiation and incidence of neonatal sepsis in Chipinge District Zimbabwe - Mugadza, Gladys; Zvinavashe, Mathilda; Gumbo, Felicity Zvanyadza; Pedersen, Babill Stray (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal sepsis is one of the leading causes of neonatal morbidity and mortality during the neonatal period especially in the first week of life. The objectives of this study were to determine early breastfeeding initiation (EBFI) and the incidence of neonatal sepsis in in the first week of life in Chipinge District, Zimbabwe. Methods: After obtaining approval from the ethical institutional review board and Medical research council of Zimbabwe, a total of 200 healthy term neonates were recruited into a prospective cohort study within 24 hours of birth after the mothers had given an informed consent. Mother and baby pair was followed up at day 3 and day 7 to assess presence of infection using clinical checklist and physical examination. Results: The Pearson correlation was significant at 0.01 level (2 tailed) at day 3 and day 7. The findings revealed a significant association between EBFI and neonatal sepsis in the first week of life. Conclusions: Neonatal sepsis is one of the leading causes of death during the neonatal period especially in the first week of life. Findings of the study revealed a significant Pearson correlation at 0.01 levels (2 tailed) at day 3 and day 7. Delayed initiation of breastfeeding increases the risk of neonatal sepsis and about 33 % neonatal deaths can be averted if breastfeeding is initiated within an hour of birth.